Large Eddy Simulation Approaches for Trailing-Edge Heat Transfer in Gas Turbine Blades: A Review - Joon Ahn (Energies)
The trailing edge of gas turbine blades encounters concentrated heat loads, necessitating cooling techniques distinct from those used in mid-chord regions. Narrow cooling channels in these areas typically incorporate pin fins or dimples for internal cooling. In contrast, external cooling relies on cutback film cooling configurations, which differ significantly from mid-chord designs. Large eddy simulation (LES) has emerged as a powerful tool for investigating heat transfer in these challenging environments, capturing intricate flow phenomena and turbulence effects that Reynolds-Averaged Navier–Stokes (RANS) simulations often cannot resolve. This review synthesizes findings from 54 LES-based studies on trailing edge cooling, focusing on three key configurations: pin fin arrays, dimpled surfaces, and cutback film cooling. LES consistently demonstrated higher accuracy in predicting heat transfer and cooling effectiveness, outperforming RANS by resolving complex flow structures such as horseshoe vortices, shear layer vortices, and unique flow interactions inherent to these geometries. Furthermore, LES provided detailed turbulence statistics and local heat transfer distributions, offering critical insights for optimizing and improving predictive models. Beyond its demonstrated capabilities, this review underscores the future potential of LES in advancing shape optimization, transient flow analysis, and multi-physics simulations, including conjugate heat transfer and flow-structure interactions.